Cytotoxicity study of reaction products between isatin and furan - Md. Arifuzzaman; Rafiya Khan Kandahary; Md. Rabiul Islam (Bangladesh Pharmacological Society, 2009)
Isatin, 5-chloroisatin, 7-bromoisatin and 7-ethylisatin on treatment with furan in presence of diethylamine yield furan moiety inclusion products bis-diisatin [3,3´] furan, bis-[5,5´] dichlorodiisatin [3,3´] furan, bis-[7,7´] dibromodiisatin [3,3´] furan and bis-[7,7´] diethyldiisatin [3,3´] furan respectively in moderate yields. The cytotoxicity of these compounds was studied by the brine shrimp lethality bioassay and the Structure Activity Relationships (SAR) of these compounds has been discussed. The present study shows that the compound bis-[7,7´] dibromodiisatin [3,3´] furan had pronounced cytotoxicity whereas compounds bis-[5,5´] dichlorodiisatin [3,3´] furan and bis-[7,7´] diethyldiisatin [3,3´] furan were moderately active. It is remarkable that the constituent, Y = -Br at seven position in the benzene ring has greater activity than ethyl and chlorine atom.